Perceptions of South Asia's visual past - Asher, Catherine B. (Catherine Blanchard), 1946-; Metcalf, Thomas R., 1934- (New Delhi : American Institute of Indian Studies, New Delhi, Swadharma Swarajya Sangha, Madras, and Oxford & IBH Pub. Co., 1994)
Seminar papers on art history; chiefly in the Indian context.
Includes bibliographical references and index.
Keywords: Art -- India, South -- Congresses; India, South -- History -- Congresses; India, South -- Civilization -- Congresses